Transformations and Challenges of Argentine Immigration Policy in Relation to the International Context - Novick, Susana (2012)
The purpose of this article is to analyze recent transformations in Argentinean migratory policies since the 2001 crisis, based on the state’s passage of laws. The first part provides a brief historical outline approach as the framework and context for interpreting the present processes, their continuities and discontinuities. It emphasizes the influence of the international scene on the development of migratory policies—“denationalization” and “renationalization”—, and the social agents involved. The article ends with a description of policy progress and setbacks, including the challenges that must be faced.